Transition from wave pattern to stationary pattern in a spatial predator-prey system with delay. (September 2015) - Wang, Caiyun; Wang, Lizhi
Highlights: A predator-prey model with delay was presented. We showed effects of delay on patterns. Pattern transition was obtained. Rich patterns are shown in a predator-prey model. Abstract: Spatial diffusion and time delay are two main important factors in biological systems. In this paper, a predator-prey model with Holling III functional response, which includes time delay and diffusion processes is presented. It was found that time delay can induce transition from wave pattern to stationary pattern. Furthermore, for different values of time delay, different types of stationary patterns are obtained in the predator-prey model. These results may be useful for us to understand the pattern transition arising from intrinsic elements in the real ecosystems.